2020
DOI: 10.1002/cmm4.1092
|View full text |Cite
|
Sign up to set email alerts
|

Numerical methods for solving the 3D Neumann problem of laser‐induced plasma evolution in a semiconductor: Direct and iteration methods

Abstract: The article is devoted to an effective numerical method for solving the 3D problem of laser‐induced plasma evolution in a semiconductor. The physical processes under consideration are accompanied by the existence of the nonlinear feedback between semiconductor characteristics. Mathematically the problem is described by the set of time‐dependent nonlinear PDEs, which involves the Poisson equation with Neumann boundary conditions. One of the problem complexities correlates with providing of well‐known solvabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Evidently, this non-linear feedback is "switched off" at zero-value electron mobility. In [30], we demonstrated that the presence of such a term plays a crucial role in the Neumann problem's solvability condition violation using DM.…”
Section: Remarkmentioning
confidence: 95%
See 2 more Smart Citations
“…Evidently, this non-linear feedback is "switched off" at zero-value electron mobility. In [30], we demonstrated that the presence of such a term plays a crucial role in the Neumann problem's solvability condition violation using DM.…”
Section: Remarkmentioning
confidence: 95%
“…It should be emphasized that the obtained results and conclusions are regardless of the particular method's implementation and have a general character because they arise from the solvability condition's violation caused by the round-off errors accumulation at using DM. It should be emphasized that in [30], the crucial influence of a convection-type term related to electron mobility on the computation's effectiveness was demonstrated, and at zero-value electron mobility, both methods (DM and IM) possessed the same high accuracy. However, in [30], the problem with homogeneous BCs or a particular case of the external electric field (EEF) action along the direction that is transverse to the optical pulse propagation direction was only considered.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation